Descriptions of three new species of Glossogobius (Teleostei: Gobiidae) from New Guinea - Hoese, Douglass F.; Allen, Gerald R. (Zootaxa, 2015)
Three new species of Glossogobius are described from New Guinea. Glossogobius multipapillus, n. sp. from northeastern New Guinea has a lobed mental fraenum and a distinctive papilla pattern unlike any other species in the genus. Glossogobius sentaniensis, n. sp. is described from Lake Sentani. The species is similar to Glossogobius aureus and G. koragensis differing in head pores and large dark spots on the body. Glossogobius macrocephalus n. sp. from Lake Tebera and surrounding rivers has a lobed mental fraenum and differs from other species in the Glossogobius celebius group in the combination of having a large head, head pore, fin-ray and predorsal scale counts.